Analysis of Complete Puumala Virus Genome, Finland - Plyusnina, Angelina (Centers for Disease Control and Prevention, 2012)
Puumala virus causes nephropathia epidemica, a rodent-borne zoonosis that is endemic to Europe. We sequenced the complete Puumala virus genome that was directly recovered from a person who died and compared it with those of viruses from local bank voles. The virus strain involved was neither a unique nor rare genetic variant.